Correct Answer - Option 1 : √(23/7)

**Given**

[(a^{4} - a^{2} + 1)/(a^{4} + a^{2 }+ 1)] = 1/8

**Concept**

Use identity: (a + b)^{2 }= a^{2} + 2ab + b^{2}

**Calculation**

[(a^{2}- 1 + 1/a^{2}]/[(a^{2}+ 1 + 1/a^{2}] = 1/8

⇒ [(a^{2}+ 1/a^{2 }+ 2) - 1 - 2]/(a^{2} + 1/a^{2 }+ 2) + 1 - 2)] = 1/8

⇒ [(a + 1/a)^{2} - 3]/[(a + 1/a)^{2} - 1] = 1/8

⇒ 8[(a + 1/a)^{2} - 3] = 1[(a + 1/a)^{2} - 1]

⇒ 8(a + 1/a)^{2 }- 24 = (a + 1/a)^{2} - 1

⇒ 8(a + 1/a)^{2} - (a + 1/a)^{2} = -1 + 24

⇒ (a + 1/a)^{2 }[8 - 1] = 23

⇒ (a + 1/a)^{2} = 23/7

⇒ (a + 1/a) = √(23/7)

**∴ Value of (a + 1/a) is √(23/7)**